2000
DOI: 10.1061/(asce)0733-9364(2000)126:1(52)
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Root Causes of Construction Accidents

Abstract: Construction accident investigation techniques and reporting systems idt:ntify what type of accidents {>ccur and how they occurred. Unfortunately, they do not properly address why the accident occurred by identifying possible root causes, which is only possible by complementing these techniques with theories of accident causation and theories of human error. The uniqueness of the construction industry dictates the need to tailor man} of the contemporary accident causation model~; and human error theorics. Tl1i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
197
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 496 publications
(241 citation statements)
references
References 9 publications
1
197
0
12
Order By: Relevance
“…According to an accident root causes tracing model (ARCTM), accidents occur due to three root causes: (1) Failing to identify an unsafe condition that existed before an activity was started or that developed after an activity was started; (2) deciding to proceed with a work activity after the worker identifies an existing unsafe condition; and (3) deciding to act unsafely regardless of the initial conditions of the work environment (Abdelhamid & Everett, 2000). The categories of measurements used for safety activity analysis are the safe behavior and condition, unsafe behavior, unsafe condition, and injury/illness.…”
Section: Categories Of Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…According to an accident root causes tracing model (ARCTM), accidents occur due to three root causes: (1) Failing to identify an unsafe condition that existed before an activity was started or that developed after an activity was started; (2) deciding to proceed with a work activity after the worker identifies an existing unsafe condition; and (3) deciding to act unsafely regardless of the initial conditions of the work environment (Abdelhamid & Everett, 2000). The categories of measurements used for safety activity analysis are the safe behavior and condition, unsafe behavior, unsafe condition, and injury/illness.…”
Section: Categories Of Measurementmentioning
confidence: 99%
“…Safety problems are related to unsafe or careless employees that can be resolved by closely monitoring and changing their behaviors (DeJoy, 2005). A worker may commit unsafe acts regardless of the initial conditions of the work (i.e., whether the condition was safe or unsafe) (Abdelhamid & Everett, 2000). Examples of unsafe worker acts include the decision to proceed with work in unsafe conditions, disregarding standard safety procedures such as not wearing a hard hat or safety glasses, working while intoxicated, or working with insufficient sleep.…”
Section: Unsafe Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 80 to 90 percent of these accidents were strongly associated with workers' unsafe behavior and acts. Behavior models and human factors approach consider human errors as being the main cause of accidents [32]. Quinn [33] studied the demographic information of field and office personnel who most frequently are involved in workplace accidents and found that 56.3 percent of accidents were caused by a lack of attention or awareness.…”
Section: Safety and Human Factormentioning
confidence: 99%